Penetapan Dosis Tepung Daun Cengkeh untuk Mengendalikan Hama Gudang Kacang Hijau (Callosobruchus Maculatus Fabricius.)(Coleoptera : Bruchidae) pada Suhu Penyimpanan yang Berbeda: Penetapan Dosis Tepung Daun Cengkeh untuk Mengendalikan Hama Gudang Kacang Hijau (Callosobruchus Maculatus Fabricius.)(Coleoptera : Bruchidae) pada Suhu Penyimpanan yang Berbeda - Evinia Norenza; Tri Lestari; Rion Apriyadi (Universitas Bangka Belitung, 2019)
Callosobruchus maculatus is a postharvest pest in storage that causes the decrease in quality of green beans. One of control technique that can be done by using clove leaf flour as a botanical insecticide at different storage temperature. The purpose of this study was to know the effect of various clove leaf doses, to know the effect of storage temperature and interaction between various doses with different storage temperatures in controlling C. maculatus. This research used the experimental method with Split Plot design which consists of 3 levels main plot and 5 levels of subplot. Each treatment has 3 replications.. The results showed that the difference of dose and temperature as well as interaction both had a very significant effect on the number of eggs, the number of imagoes and the percentage of seed damage. Water content increased at temperatures ± 15 ºC and decreased at temperatures ±35ºC. The conclusion of this research is clove leaf flour gave effect to mortality of pest C. maculatus, storage temperature effect on mortality of pest C. maculatus, clove leaf dose 5 g per 100 g green beans and storage temperature ± 15 ºC is the best combination in controlling pest C. maculatus on green beans.